Upholding a Code Not Their Own: Non-Muslim Minority Leadership in the Internalization of Islamic Organizational Culture - Rizkia, Fadila Nur; Setianti, Yanti; Nugraha, Aat Ruchiat (LPPM Universitas Jambi, 2026)
Studies of Islamic work culture generally assume that religious values are best transmitted by leaders sharing the majority's faith. This ethnographic study questions this assumption by examining PT X, a sharia-oriented startup where a Christian Chief Operating Officer (COO) models and enforces Manhaj Salaf principles. Using NVivo-assisted analysis integrating Hymes, Philipsen, and Schein, we investigate how this minority leader communicates and internalizes a majority-religion code. Findings reveal that to navigate a tense environment marked by collective employee silence and harsh CEO directives, the COO employs a protective communication strategy. He acts as a structural